Motivating Literacy and Literary Skills in Students for Remediation: An Innovative and Foregrounding Approach - Abubakar, Amina (American Journal of Education and Practice, 2022)
Purpose: Innovative And Foregrounding Approach to Motivating Literacy and Literary Skills (IFAMLSIS) provides a summary of the writer's foreground approach to motivating students on the core aspects of reading, writing and literary skills spectacled from an innovative skills program. The module, an action research, was developed as part of remediation program for students who lacked the proficiency in English language in the Department of English of the Federal College of Education Kano, Nigeria. The focus of this review is on the fundamental components of reading, writing, and literary abilities as seen through the lens of a novel Foregrounding Approach. It has been developed with purposeful activities that are meant to ground students in the skill of reading and enjoying literary texts, which in turn, are imagined, would change them into competent writers. Methodology: The module's operation is based on the collaborative "Think-Pair-Share" model, which allows students to work or navigate through assignments independently at first, then in pairs, groups, or as a class, as well as share ideas and cooperate on tasks and projects. Findings: The researcher reveals the several modules created for remediation for students with deficiencies in English language. Each part includes thorough explanations and summaries of the contents of each unit. Also included are suggestions for the implementation of the program as well as its advantages, particularly for ESL students. Contribution to theory: Although the module's implementation is still in development, it is anticipated that the results will be favorable. The module will be improved using the results of its pilot testing. The government, the commercial sector, and other stakeholders in higher education are urged to contribute financially to the publication, mass manufacturing, and distribution of the module throughout Nigerian colleges of education and elsewhere.